Thomas Carlyle's Calvinist dialogue with the nineteenth-century periodical press. Issue 1 (2nd January 2019) - Malecka, Joanna
ABSTRACT: This article signals at a dearth of critical engagement with Thomas Carlyle's Presbyterian heritage resulting from the received whiggish narrative of his Calvinism as unenlightened, anachronistic, and backward-looking. It proceeds to challenge this view by examining closely Carlyle's creative use of key Calvinist concepts in his cosmopolitan and enlightened dialogue with the contemporary periodical press over British and European cultures. Carlyle is shown to be an adept purveyor both of the Edinburgh Magazine 's enlightened idiom and of Blackwood's morally conservative and artistically cosmopolitan agendas, while also making creative capital of the Anti-Jacobin 's powerful Gothic imagery and of the critical verve of the Westminster Review . The main addressees of Carlyle's reading of the signs of the times, I argue, are contemporary Whigs. Carlyle's depiction of Macaulay as a 'spiritual hippopotamus' spells Carlyle's broader critique of the modern lack of imagination of the spiritual which sponsors deterministic religious and secular readings of reality. Carlyle displays his enlightened Calvinist perspective in discussing the French Revolution through such key Scottish Enlightenment concepts as free will, conscience, civilisational and moral progress, and divine providence. Insightful and creative use of his inherited Scottish Calvinist heritage characterises Carlyle's open, cosmopolitan reading of the signs of the times.